2014
DOI: 10.1161/circresaha.114.302319
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Phospholipase A 2 Receptor Increases Susceptibility to Cardiac Rupture After Myocardial Infarction

Abstract: Rationale: Recent evidence indicates that the biological effects of secretory phospholipase A 2 (sPLA 2 ) cannot be fully explained by its catalytic activity. A cell surface receptor for sPLA 2 (PLA 2 receptor 1 [PLA 2 R]) and its high-affinity ligands (including sPLA 2 -IB, sPLA 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
4
30
2
Order By: Relevance
“…In the early phase of myocardial infarction, cardiac fibroblast proliferation prevents cardiac rupture, improves the survival rate, and promotes cardiac repair. 38,39 Growing evidence shows that expansion of the inflammatory response results in cardiomyocyte death, deterioration in remodeling, and dysfunction after myocardial infarction through the release of reactive oxygen species, matrix metalloproteinase, and pro-inflammatory cytokines, 40 In this study, we demonstrate that a mir-155 deficiency increased fibroblast proliferation and collagen synthesis and reduced the inflammatory response, which would likely decrease the incidence of cardiac rupture in the early stage of myocardial infarction and improve cardiac function. Importantly, the transfusion of macrophage-derived exosomes to mir-155 À/À mice recovered mir-155 expression in the heart and increased the incidence of cardiac rupture ( Figure 6).…”
Section: Mmp3mentioning
confidence: 59%
“…In the early phase of myocardial infarction, cardiac fibroblast proliferation prevents cardiac rupture, improves the survival rate, and promotes cardiac repair. 38,39 Growing evidence shows that expansion of the inflammatory response results in cardiomyocyte death, deterioration in remodeling, and dysfunction after myocardial infarction through the release of reactive oxygen species, matrix metalloproteinase, and pro-inflammatory cytokines, 40 In this study, we demonstrate that a mir-155 deficiency increased fibroblast proliferation and collagen synthesis and reduced the inflammatory response, which would likely decrease the incidence of cardiac rupture in the early stage of myocardial infarction and improve cardiac function. Importantly, the transfusion of macrophage-derived exosomes to mir-155 À/À mice recovered mir-155 expression in the heart and increased the incidence of cardiac rupture ( Figure 6).…”
Section: Mmp3mentioning
confidence: 59%
“…Pla2r1 Ϫ / Ϫ mice show lower infl ammation after LPS challenge through some unknown mechanism ( 150 ). In a model of allergen-induced asthma, the lungs of Pla2r1 Ϫ / Ϫ mice show greater infi ltration of immune cells and higher levels of eicosanoids and Th2 cytokines, accompanied by greater levels of sPLA 2 -IB and -X proteins, than those of wild-type mice ( 151 ), providing the fi rst in vivo evidence that PLA2R1 serves as a clearance receptor for these sP-LA 2 s. In a model of myocardial infarction, Pla2r1 Ϫ / Ϫ mice exhibit higher rates of cardiac rupture, with impaired collagen-dependent migration, growth, and activation of myofi broblasts ( 152 ). Mechanistically, binding of sPLA 2 -IB to PLA2R1 augments the migration and growth of myofibroblasts, and thereby wound healing, through functional interaction with integrin, supporting the signaling role of PLA2R1.…”
Section: Discussionmentioning
confidence: 95%
“…Our data showed that the increased incidence of cardiac rupture observed in Girdin SA/SA mice might be attributable to impaired recruitment of myofibroblasts to the infarcted area. In fact, prior studies have revealed that adaptive fibrosis in the infarcted area prevents cardiac rupture [28,29]. For example, Hofmann et al reported that the osteogenesis imperfecta mouse model, which lacks procollagen-α2(I) expression, exhibits increased mortality due to higher incidence of cardiac rupture, and deficiency of collagen type I leads to a myocardial wound-healing defect [30].…”
Section: Discussionmentioning
confidence: 99%